Q. 474.7( 3 Votes )

Solve the followi

Answer :

In factorization, we write the middle term of the quadratic equation either as a sum of two numbers or difference of two numbers such that the equation can be factorized.



x(x – 1 + 2x – 4) = 6(x2 -3x + 2)


3x2 - 5x = 6x2 – 18x + 12


3x2 - 13x + 12 = 0


3x2 - 9x - 4x + 12 = 0


3x(x - 3) -4(x – 3) = 0


(3x – 4)(x – 3) = 0


x = 4/3, 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses